Simulation model for studying the parameters of sensor network traffic transmission using the LoRaWAN protocol - G. I. Linets; S. V. Melnikov; G. V. Slyusarev; S. V. Govorova; D. A. Avdonin; V. A. Gromakov (Современная наука и инновации, 2024)
The article proposes a simulation model of data transmission of the LoRaWAN network in the boundary gateway - transport network – remote server section. The implemented model is based on the Linux operating system, the process of simulating a transport network is carried out by standard tools such as "tc" (Traffic Control) using the "NetEm" utility. This utility allows you to emulate phenomena such as: loss, transmission delays, reordering, packet distortion, as well as other factors that distort transport layer packets.